Improving Student Learning Outcomes Through A Problem-Based Learning Model on The Subject PKN Theme 9 The Rich of My Country For Primary School Students - Hasni Hasni; Yurfiah Yurfiah; La Ode Madiani (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
The motivation behind this review is to further develop Civics learning outcomes through a problem-based learning model in class IV at Elementary School Country 3 Katobengke. This kind of exam is a kind of research activity for the homeroom teacher (Vehicles) with exploration subjects in class IV of Elementary School Country 3 Katobengke with a total of 34 students. The aim of this exam is to further develop student learning outcomes with material about freedom and commitment to clean water accessibility. Judging from the results of the review, student learning outcomes in the pre-cycle were 38.23% (13 students) with a typical score of 61.17%. In the primary cycle, student learning outcomes increased to 64.70% (22 students) with an average score of 71.32%. In cycle II student learning outcomes increased to 85.29% (29 students) with an average score of 80.23%. Therefore, it can be assumed that by implementing a problem-based learning model, student learning outcomes can be further developed in the PKN subject topic 9 Kaya Bangsa in class IV of Elementary School Country 3 Katobengke.